Synergy Between Crop Competition Agronomic Practices and Herbicides for Effective Weed Control in Plant Production - Pacanoski, Zvonko (Acta herbologica, 2019)
Interaction of herbicide applications with the manipulation of certain agronomic practices for crop competition, including sowing date and seeding rate, row and plant spacing, and application of fertilizers have the potential to reduce the abundance of agricultural weeds and optimize herbicide use. Sowing date and herbicide application play a significant role in determining growth, development and seed yield of many crops as well as reducing weed density and weed biomass. Narrow row spacing can improve weed control because weeds are smaller and more easily controlled with herbicides than they are in wide row spacing. Further, the more rapid crop canopy development of narrow- row spacing reduces problems with late emerging weeds and may allow POST EM herbicides to be applied earlier in the season, therefore improving effectiveness and allowing reduced rates to control small weeds. Finally, adequate fertilization increases the vigour and competitiveness of the crop. By altering the time and method of fertilizer with herbicide application, competitive advantage can be shifted in favour of the crop.